Pulpal and periapical diseases experience in a central Brazilian population - Lorena Frange Caldas; Giulliano Caixeta Serpa; Lucas Rodrigues de Araújo Estrela; Daniel de Almeida Decurcio; Helder Fernandes de Oliveira; Cyntia Rodrigues de Araújo Estrela; Orlando Aguirre Guedes (Revista Sul-Brasileira de Odontologia, 2021)
Diseases of the pulp and periapical tissues comprise the major reasons for seeking emergency dental care services. Objective: This retrospective cross-sectional study aimed to investigate the prevalence of pulpal and periapical diseases in a central Brazilian population. Material and methods: The sample was comprised of patients treated at the Basic Attention Integrated Clinic of the Dental School of the Universidade de Cuiabá, between 2011 and 2015. The following information was collected from the patients’ records: sex, age, tooth, anatomical location, and the pulpal or periapical diagnosis. The statistical analysis included frequency distribution and cross-tabulation. The data were analyzed by using χ2 tests. The level of significance was set at 5% for all analyses. Results: The analysis involved 1,277 patients (822 female; 64.4%), aged between 6 and 78 years old. The highest frequency of pulpal and periapical diseases was observed in patients aged 21 to 30 years old (n = 389; 30.5%). A total of 1,488 pulpal and periapical diseases was recorded. Symptomatic pulpitis (n = 467; 31.4%) and infectious symptomatic apical periodontitis (n = 456; 30.6%) were the most common type of diseases. Seven hundred and sixty-seven affected teeth (51.5%) were maxillary teeth, and 1,247 (83.8%) were located in the jaws’ posterior region. The most affected teeth were the mandibular molars (n = 516; 34.7%) and maxillary molars (n = 355; 23.9%). Statistically significant difference was observed between the type of pulpal and periapical disease and sex, age, anatomical location (anterior or posterior), and tooth (p < 0.05). Conclusion: There was a higher prevalence of pulpal and periapical diseases in female individuals aged between 21 and 30 years old and involving teeth located in the posterior region of the jaw.